Desentralisasi dan Ketidakefektifan Penegakan Hukum Lingkungan: Analisis Politik Pemerintahan atas Kasus Sungai Citarum - Alwi Al Hadad (Fakultas Politik Pemerintahan, 2025)
This study aims to analyze the relationship between decentralization and the ineffectiveness of environmental law enforcement in the case of Citarum River pollution. Although a national legal framework exists, implementation at the local level reveals weak institutional capacity, poor inter-agency coordination, and low accountability of local governments. This research employs a qualitative approach using a case study method in the Citarum River Basin. The findings indicate that decentralization has not fully strengthened environmental law enforcement due to weak political will, the dominance of economic interests, and limited public participation. The study recommends strengthening local governance through policy reform, institutional capacity building, and greater public involvement in environmental oversight.